2020
DOI: 10.1007/s00408-019-00299-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating P-Selectin Glycoprotein Ligand 1 and P-Selectin Levels in Obstructive Sleep Apnea Patients

Abstract: Purpose Obstructive sleep apnea (OSA) is characterized by chronic intermittent hypoxia which induces inflammation in blood vessels leading to the development of cardiovascular comorbidities. Several studies implicated the role of P-selectin in vascular inflammation of OSA. P-selectin glycoprotein ligand 1 (PSGL-1) is the main activator for P-selectin and is involved in immune cell trafficking. However, PSGL-1 has not been analyzed in OSA. The aim of the study was to investigate plasma PSGL-1 and P-selectin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…The degradation of HMW-HA under inflammatory conditions reduces extracellular HA viscosity and increase tissue permeability 34 resulting extravasation of macrophages to the arterial wall. The damaged endothelium facilitates the adhesion of leukocytes and platelets via adhesion molecules, and the levels were found to be elevated in OSA 2,35 . Dogné et al demonstrated that the lack of HYAL-1 is associated with lower levels of P-selectin suggesting that HYAL-1 deficiency may be protective in endothelial dysfunction 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of HMW-HA under inflammatory conditions reduces extracellular HA viscosity and increase tissue permeability 34 resulting extravasation of macrophages to the arterial wall. The damaged endothelium facilitates the adhesion of leukocytes and platelets via adhesion molecules, and the levels were found to be elevated in OSA 2,35 . Dogné et al demonstrated that the lack of HYAL-1 is associated with lower levels of P-selectin suggesting that HYAL-1 deficiency may be protective in endothelial dysfunction 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnoea (OSA) is the most common sleep-related breathing disorder which is characterised by the repetitive collapse of the upper airways during sleep resulting in chronic intermittent hypoxaemia (CIH) and frequent arousals with sleep fragmentation. These factors lead to enhanced oxidative stress and consequential systemic inflammation which are associated with altered concentrations of circulating pro-inflammatory 1 , 2 and anti-inflammatory 3 , 4 biomarkers. Understanding the role of inflammation in OSA is of importance as it could be a link to the development of cardiometabolic comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Korábbi kutatásokhoz ha-sonlóan a CRP-szintek vizsgálatunkban is szignifikánsan magasabbnak bizonyultak az OSA-ban szenvedő résztvevők körében a kontrollcsoporthoz képest [26]. A CRP mellett számos proinflammatorikus citokin és biomarker (például adhéziós molekulák, komplementek) magasabb szintjét igazolták OSA-ban [27,28].…”
Section: Megbeszélésunclassified
“…In 2020, we published two articles on pediatric obstructive sleep apnea syndrome (OSAS) [ 5 , 27 ], including a State-of-the-Art review on the evaluation and management of children with OSAS [ 5 ]. Studies in adult OSAS included therapy [ 79 ], adherence [ 76 ], risk of occupational injury [ 78 ], and possible associated biomarkers [ 75 , 77 , 80 ].…”
mentioning
confidence: 99%